2020
DOI: 10.12657/denbio.084.003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of pollen shedding for longleaf pine (Pinus palustris) at the Escambia Experimental Forest in Alabama, USA

Abstract: Longleaf pine is an important tree species in the southeastern United States and studying the temporal patterns of pollen shedding is crucial to a better understanding of its phenology and seed production. In this study, field observation data on the timing of pollen shedding from 1958 to 2013 were analyzed with reference to local weather conditions. Our results indicated that the time of peak pollen shedding after January 1 (TPPS) ranged from 53 days (about February 22) to 95 days (around April 5). There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The male catkins and female conelets of longleaf pine initiate in July and August and develop during subsequent months (Guo et al, 2016). Pollen shedding occurs around March (Boyer, 1973;Chen et al, 2020), but fertilization does not occur until the following spring, and maturation and dispersal occur c. 2.5 yr after initiation in October (Chen et al, 2018). Because of the prolonged development time, newly initiated catkins and conelets (c. 2 months old) and recently pollinated conelets (c. 14 months old) are both present during the period of peak TC activity (August-September).…”
Section: Discussionmentioning
confidence: 99%
“…The male catkins and female conelets of longleaf pine initiate in July and August and develop during subsequent months (Guo et al, 2016). Pollen shedding occurs around March (Boyer, 1973;Chen et al, 2020), but fertilization does not occur until the following spring, and maturation and dispersal occur c. 2.5 yr after initiation in October (Chen et al, 2018). Because of the prolonged development time, newly initiated catkins and conelets (c. 2 months old) and recently pollinated conelets (c. 14 months old) are both present during the period of peak TC activity (August-September).…”
Section: Discussionmentioning
confidence: 99%
“…Although pollen and unfertilized conelets do not have a temporal cycle, the sex allocation ratio between male and female structures is positively correlated with temperature, and cone production is optimal when this ratio is intermediate [26] . Chen et al [5] revealed no significant trend in either the time of peak pollen shedding or time of 80% accumulated pollen density over 55 years of data. However, the time of peak pollen shedding was connected to climate factors, primarily the heat sum of total days above 0 °C.…”
Section: Pre-fertilization Trendsmentioning
confidence: 96%
“…In botany, both the timing of growing seasons and reproduction are known to vary with climate [33,55] . Factors associated with reproduction in plants such as time of pollen release, fertilization, and intraspecific interactions are known to vary by species, and the impact of climate on these factors varies as well [1,5,56,57] . For example, in angiosperms, changing temperature variables can lead to altered seasonal timing between plant flowering and pollinator activity and composition [54] .…”
Section: Pre-fertilization Trendsmentioning
confidence: 99%
See 2 more Smart Citations